2008
DOI: 10.19173/irrodl.v9i2.516
|View full text |Cite
|
Sign up to set email alerts
|

Online Self-Regulatory Learning Behaviors as a Mediator in the Relationship between Online Course Perceptions with Achievement

Abstract: Positive perceptions of online course communication and collaboration have been associated with better academic outcomes, while self-regulatory learning behaviors have also been linked to academic achievement and other positive learning outcomes. In the current study, we examined whether self-regulatory learning behaviors may be considered as mediating the relationship between student perceptions of online course communication and collaboration with academic achievement as measured by grade point average (GPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 18 publications
(25 reference statements)
2
94
0
10
Order By: Relevance
“…In his triadic analysis of 114 SRL, he described the interrelations between people, the environment, and self-regulated behavior from a social-cognitive perspective. Later studies (e.g., Barnard, Paton, & Lan, 2008;Pintrich & De Groot, 1990;Zimmerman & Schunk, 2001) confirm this analysis in the sense of the context-specificity of SRL. This context-specificity is confirmed in our study, which shows a positive relationship between the perceived flexibility of learning and SRL strategies in an ODL setting.…”
Section: Discussionmentioning
confidence: 75%
“…In his triadic analysis of 114 SRL, he described the interrelations between people, the environment, and self-regulated behavior from a social-cognitive perspective. Later studies (e.g., Barnard, Paton, & Lan, 2008;Pintrich & De Groot, 1990;Zimmerman & Schunk, 2001) confirm this analysis in the sense of the context-specificity of SRL. This context-specificity is confirmed in our study, which shows a positive relationship between the perceived flexibility of learning and SRL strategies in an ODL setting.…”
Section: Discussionmentioning
confidence: 75%
“…The OSLQ was developed considering the accuracy and reliability of the results from the data sample collected [36,37].…”
Section: Measuring Self-regulated Learning Skillsmentioning
confidence: 99%
“…Exploring the perceptions of self-regulatory learning behaviours have been associated to better academic attainment and imperative to achieving better learning outcomes. In the current study we investigate whether self-regulatory learning patterns could be seen as mediation in the relationship to attaining better grades and distinguish the different levels of self-regulated learning dimensions [2]. The results indicated that students' dimensions of online self-regulatory learning patterns, although not totally conclusive on the education achievement in themselves, do shows the relationship of the perceptions of online blended learning course to academic improvement.…”
Section: Introductionmentioning
confidence: 85%
“…It is however essential to mention that task specific strategies planned by the learners help to support learning reflection, self-direct their studies and reflecting during the learning process [26]. Environment structuring is said to follow implicit behaviour by eliminating all elements of distractions from the learning environment [2,36]. Self-evaluation strategy is similar to component of selfjudgement.…”
Section: Measuring Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation